Adaptively tuned vibration absorber using cone based continuously variable transmission. Issue 1 (31st December 2022) - Punyakaew, Surat
Abstract: In this paper, a new adaptive tuned vibration absorber (ATVA) design is presented for suppressing the resonance of primary system. A cone-based continuously variable transmission (cone CVT) is proposed to integrate a dynamic vibration absorber (DVA) for retuning itself in response to a time-varying excitation frequency. The natural frequency of ATVA can be dynamically tuned over a wide range by varying the gear ratio of the cone CVT, resulting in a change in the system's net mass moment of inertia. To predict the system response for various design parameters, a mathematical model is developed. The simulation of this model is employed through MATLAB software. The analytical model is numerically evaluated by tuning the frequency from 3.27 to 7.43 Hz. The results indicate that the proposed scheme may greatly increase the frequency bandwidth of the absorber while also suppressing the primary system's resonance. This indicates that the work is applicable to ATVA's practical applications.